PENGARUH BRAND IMAGE TERHADAP LOYALITAS KONTRIBUTOR PT. SEMEN BATURAJA (PERSERO) TBK DENGAN MEDIASI LAYANAN DAN KEPUASAN KONSUMEN - Mediarta, Yogi Artha; Zamzam, Fakhry; Rostiati, Neny (Jurnal Ecoment Global, 2020)
This study aims to see the effect of brand image on the loyalty of contributors of PT. semen baturaja (persero) tbk with service mediation and customer satisfaction. This research uses quantitative data analysis methods in the form of descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that the brand image that uses Baturaja cement is safer, has a positive and significant effect on providing services by SMBR is reliable; has a significant effect on improving the service of consumers who have experienced selling Baturaja cement which is more profitable; has a positive and significant effect on consumer loyalty to the brand image of Baturaja cement is always superior; consumer satisfaction because selling Baturaja cement is more profitable, has a positive and significant effect on distributor loyalty which is formed from the image of the Baturaja cement brand that is always superior; and that the brand image of the use of Baturaja cement is much safer, the quality of customer service is improved by offering reliable service and customer satisfaction so that selling Baturaja cement is always more profitable. Has a significant effect on increasing the loyalty of Semen Baturaja distributors by maintaining the brand image of Baturaja Cement so that it is always superior.Â Keywords: Brand Image, Loyalty, Service Mediation, Customer Satisfaction, PT. Semen Baturaja